Evolution semigroups for nonautonomous Cauchy problems - Gregor Nickel (Abstract and Applied Analysis)
In this paper, we characterize wellposedness of nonautonomous, linear Cauchy problems (NCP)  {u˙(t)=A(t)u(t)u(s)=x∈X on a Banach space X by the existence of certain evolution semigroups.